2017
DOI: 10.1039/c7sm01533j
|View full text |Cite
|
Sign up to set email alerts
|

Tunable synthetic control of soft polymeric nanoparticle morphology

Abstract: With a growing variety of nanoparticles available, research probing the influence of particle deformability, morphology, and topology on the behavior of all polymer nanocomposites is also increasing. In particular, the behavior of soft polymeric nanoparticles in polymer nanocomposites has displayed unique behavior, but their precise performance depends intimately on the internal structure and morphology of the nanoparticle. With the goal of providing guidelines to control the structure and morphology of soft p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…The interdiffusion of deuterated polystyrene (d-PS) and protonated polystyrene soft nanoparticles (h-PS NP) was monitored with d-PS-SNP bilayer thin films, where the details of the protocol are described in our previous publications. , Deuterated polystyrene with molecular weight ( M w ) 125000 g/mol was purchased from Polymer Source, while toluene (Spectroscopic grade) was purchased from Sigma-Aldrich, and both were used as received. The soft nanoparticles used in this study were synthesized by monomer-starved semibatch nanoemulsion polymerization, where the details of the synthesis are described in the literature. , During the synthesis of the NPs, the monomer addition rate (time) and percentage of divinylbenzene (DVB) cross-links added during the polymerization can be varied, resulting in NPs with different cross-link density and molecular weight. Formation of SNP with different cross-link density produced nanoparticles with different softness, with a lower cross-link density corresponding to a softer nanoparticle.…”
Section: Methodsmentioning
confidence: 99%
“…The interdiffusion of deuterated polystyrene (d-PS) and protonated polystyrene soft nanoparticles (h-PS NP) was monitored with d-PS-SNP bilayer thin films, where the details of the protocol are described in our previous publications. , Deuterated polystyrene with molecular weight ( M w ) 125000 g/mol was purchased from Polymer Source, while toluene (Spectroscopic grade) was purchased from Sigma-Aldrich, and both were used as received. The soft nanoparticles used in this study were synthesized by monomer-starved semibatch nanoemulsion polymerization, where the details of the synthesis are described in the literature. , During the synthesis of the NPs, the monomer addition rate (time) and percentage of divinylbenzene (DVB) cross-links added during the polymerization can be varied, resulting in NPs with different cross-link density and molecular weight. Formation of SNP with different cross-link density produced nanoparticles with different softness, with a lower cross-link density corresponding to a softer nanoparticle.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the shape, is well known that spherical nanoparticles are readily internalized nanosystems [ 64 , 65 ]. Regarding micelles nanosystems the information about cell internalization is still contradictory [ 41 ]. However, a study performed by Geng et al[ 66 ] demonstrated that nanomicelles are also internalized.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the fact that nanosystems shows a large surface area [ 35 – 37 ], allowing a highly payload [ 38 , 39 ] with specific antiviral drugs increasing the efficacy is a desired effect. The tunable surface charge [ 40 , 41 ] which increases the cellular trafficking [ 42 , 43 ], allowing the intracellular effect is also quite desirable. Nonetheless, is important to notice that nanosystem may be constructed to biomimetic several targets: cell, virus and bacteria, increasing the therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Architecting the suitable surface state, on another hand, of nanoparticles with active/functional components that intensify interfacial interactions are required for controlled and specific assemblies. [ 12–15 ] Therefore, the interface (as initial and essential contact of interest) of the constituent nano objects of assemblies playing a crucial role in determining the strength of the interfacial interactions to form the preferred nanoscale assembly systems.…”
Section: Introductionmentioning
confidence: 99%